Perceptions of nurses in Japan toward their patients' expectations of care: A qualitative study - Mayumi Uno; Tomomi Tsujimoto; Tomoko Inoue (Elsevier, 2017)
Objectives: This study aimed to investigate ideal nurse involvement based on the expectations of patients. Data on conflicts between nurses and patients were obtained. The patient situation involved standard nursing treatment, rather than acute phase or palliative care. Methods: Questionnaires were distributed among senior nurses attending a series of trainings in 2012 and 2013. The nurses were requested to return their completed questionnaires within two weeks. We ensured the effectiveness of the interview process to obtain accurate answers.The sample comprised 240 head nurses and assistant head nurses who were asked to respond anonymously to 57 questions about non-acute (stable) psychiatric or physical nurse-patient scenarios. Qualitative data analysis was conducted using these responses. Results: We received 41 completed responses (response rate = 17.1%). The expectations of patients and their families were reflected in five categories, namely, inference, empathic understanding, listening attitude, individual treatment, and reliable skills and explanations. Inference was independently categorized as a particularly strong characteristic of Japanese patients' expectations. Conclusions: Nursing care in situations where conflicts or misunderstandings may arise can be improved by encouraging nurses to be attentive to the moods, feelings, and expectations of patients and their families. The findings from this study can improve the quality of Japanese nursing care with regard to sensing (inferring) and reacting to the expectations of patients. Keywords: Emotions, Empathy, Humans, Nurse-patient relations, Patient care, Qualitative study